Overall Survival of Patients with Advanced Pancreatic Cancer Improved with an Increase in Second-Line Chemotherapy after Gemcitabine-Based Therapy - Zhang, Yuan-dong; Yang, Qiong; Jiang, Zhi-min; Ma, Wen; Zhou, Si-wei; Xie, De-rong (JOP. Journal of the Pancreas, 2011)
Context In the last decade, gemcitabine-based regimen as first-line therapy has demonstrated low efficacy regarding overall survival benefit for patients with advanced pancreatic cancer. Objective The purpose of this study was to explore a new strategy, such as an increased second-line chemotherapy rate, in order to improve overall survival. Design Retrospective data analysis. Methods The data in the literature on gemcitabine-based therapy for patients with advanced pancreatic cancer were collected by searching databases, such as MEDLINE, EMBASE, the Chinese Biomedical Literature Analysis and Retrieval System, and EBM Reviews (Cochrane Database of Systematic Reviews). Linear regression was used to explore the relationship between overall survival and second-line chemotherapy. The primary endpoint was overall survival. The secondary endpoints were progression-free survival and residual survival. Results Ten randomized controlled trials, involving 2,679 patients, were included in the present study. The results indicated that overall survival was positively correlated with a combination of chemotherapy, stage of disease and second-line chemotherapy in patients with advanced pancreatic cancer (r=0.753; P=0.003). Meanwhile median overall survival would be prolonged about 1.56 days if second-line chemotherapy was increased by 1% (t=4.33; P=0.001). Progression-free survival was not significantly correlated with second-line chemotherapy (r=0.092; P=0.701); in contrast, residual survival was positively correlated with second-line chemotherapy (r=0.717; P<0.001). Conclusions Our study indicated that overall survival closely correlated to second-line chemotherapy in patients with advanced pancreatic cancer; more attention should be paid before a second-line therapy which must be administered skillfully in order to improve overall survival, and this is worthy of further study. Image: Selection of randomized controlled trials.